Find an Online Tutor Now

Student H.

asked • 04/15/18

If ∫ g(x) dx from a to b = 4a+b, then ∫ (g(x)+7) dx from a to b = ?

If ∫ g(x) dx from a to b = 4a+b, then ∫ (g(x)+7) dx from a to b = ? please explain

2 Answers By Expert Tutors

By:

Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.
Most questions answered within 4 hours.

OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.